Laser powder bed fusion for metal additive manufacturing: perspectives on recent developments - Sing, Swee Leong (2021)
While significant progress has been made in laser powder bed fusion (L-PBF) for metal additive manufacturing (AM), there is still limited large scale adoption of this advanced manufacturing technique by the industry. This paper covers the recent developments in L-PBF with discussions from the materials and process perspectives. High entropy alloys and high strength aluminium alloys have been identified as key materials development for L-PBF. Then, scanning strategies and multi-lasers applications for the process are also discussed. Other research trends and topics such as powder recycling, shape memory alloys and magnetic alloys are illustrated. The final part of this paper provides an outlook on the recent advancements while suggesting potential research topics for L-PBF.